Standardising definitions for the pre-eclampsia core outcome set: A consensus development study - Duffy, JMN; Cairns, AE; Magee, LA; von Dadelszen, P; van 't Hooft, J; Gale, C; Brown, M; Chappell, LC; Grobman, WA; Fitzpatrick, R; Karumanchi, SA; Lucas, DN; et al. (Elsevier, 2020)
Objectives: To develop consensus definitions for the core outcome set for pre-eclampsia.